2020
DOI: 10.1002/aenm.202001064
|View full text |Cite|
|
Sign up to set email alerts
|

Rational Construction of Self‐Standing Sulfur‐Doped Fe2O3 Anodes with Promoted Energy Storage Capability for Wearable Aqueous Rechargeable NiCo‐Fe Batteries

Abstract: Aqueous rechargeable Ni‐Fe batteries featuring an ultra‐flat discharge plateau, low cost, and outstanding safety characteristics show promising prospects for application in wearable energy storage. In particular, fiber‐shaped Ni‐Fe batteries will enable textile‐based energy supply for wearable electronics. However, the development of fiber‐shaped Ni‐Fe batteries is currently challenged by the performance of fibrous Fe‐based anode materials. In this context, this study describes the fabrication of sulfur‐doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 76 publications
1
28
0
Order By: Relevance
“…Yang et al calculated the bandgap of Fe 2 O 3 materials, where it decreased from 2.34 to 1.18 eV after sulfur doping, resulting in improved electronic conductivity. [69] It is clearly shown in Figure 10d that the oxygen atom was partially replaced by the sulfur atom. Compared with undoped Fe 2 O 3 , the SEM image of S-Fe 2 O 3 appeared to be marginally different, with Fe 2 O 3 nanowires distributed vertically on the surface of the CNT fiber, as shown in Figure 10e.…”
Section: Niàfe Batteriesmentioning
confidence: 94%
See 1 more Smart Citation
“…Yang et al calculated the bandgap of Fe 2 O 3 materials, where it decreased from 2.34 to 1.18 eV after sulfur doping, resulting in improved electronic conductivity. [69] It is clearly shown in Figure 10d that the oxygen atom was partially replaced by the sulfur atom. Compared with undoped Fe 2 O 3 , the SEM image of S-Fe 2 O 3 appeared to be marginally different, with Fe 2 O 3 nanowires distributed vertically on the surface of the CNT fiber, as shown in Figure 10e.…”
Section: Niàfe Batteriesmentioning
confidence: 94%
“…Reproduced with permission. [69] Copyright 2020, Wiley-VCH. and numerous technical barriers persist.…”
Section: In Situ Characterization Of Energy-storage Mechanismsmentioning
confidence: 99%
“…Yang et al found that the band gap was reduced from 2.34 to 1.18 eV after the sulfur doping via the first-principle calculations, thus increasing the electronic conductivity. [60] Figure 6d clearly showed that the sulfur atoms partially replace oxygen atoms. The SEM image of SÀ Fe 2 O 3 seemed slightly different compared to the un-doped Fe 2 O 3 , where the Fe 2 O 3 nanowires were almost vertically distributed on the surface of CNTF as shown in Figure 6e.…”
Section: Iron Oxidesmentioning
confidence: 98%
“…[152] By contrast to other nonmetal elements, the sulfur displays much larger covalent radius, which may significantly enlarge the interlayer distance of carbon, offer additional ion storage sites and improved ion diffusion kinetics. [153] Due to the low electronegativity and high electron-donating ability, the phosphorus can be also doped into carbon materials to improve the electrochemical property. [154] As the same periodic element with carbon, the nitrogen is more likely to chemically bond with carbon, and effectively enhance the reactivity and electronic conductivity by producing extrinsic defects.…”
Section: Nonmetal Dopingmentioning
confidence: 99%